Chromophores, fluorophores and robust ancillary ligands for molecular catalysts: 1,3-Bis(2-pyridylimino)isoindolines - Sauer, Désirée C.; Melen, Rebecca L.; Kruck, Matthias; Gade, Lutz H. (European journal of inorganic chemistry, 2014)
Abstract Since the first report in the early 1950s, 1,3-bis(2-pyridylimino)isoindolines (BPIs) have found widespread applications in organic, inorganic and materials chemistry. This microreview focuses on recent progress towards chiral BPI derivatives as ligands for enantioselective catalysis as well as developments in the use of BPI complexes in materials science, focusing on luminescent and birefringent materials.